2011
DOI: 10.1128/mcb.01117-10
|View full text |Cite
|
Sign up to set email alerts
|

SR Proteins Induce Alternative Exon Skipping through Their Activities on the Flanking Constitutive Exons

Abstract: SR proteins are well known to promote exon inclusion in regulated splicing through exonic splicing enhancers. SR proteins have also been reported to cause exon skipping, but little is known about the mechanism. We previously characterized SRSF1 (SF2/ASF)-dependent exon skipping of the CaMKII␦ gene during heart remodeling. By using mouse embryo fibroblasts derived from conditional SR protein knockout mice, we now show that SR protein-induced exon skipping depends on their prevalent actions on a flanking constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 47 publications
5
63
0
1
Order By: Relevance
“…Interestingly, our data obtained with the SRSF1 pseudo-RRM alone fit perfectly with the above-mentioned mode of action of SR proteins in splicing regulation (22). Indeed, the binding of SRSF1 pseudo-RRM to the alternative exon of IGF1 itself activates its inclusion (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Interestingly, our data obtained with the SRSF1 pseudo-RRM alone fit perfectly with the above-mentioned mode of action of SR proteins in splicing regulation (22). Indeed, the binding of SRSF1 pseudo-RRM to the alternative exon of IGF1 itself activates its inclusion (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Their binding to intronic sequences was reported primarily to promote exon skipping (58), but the effect of their interaction with exonic sequences seems to be more complex. It was proposed that the binding of SR proteins to alternative exons promotes their inclusion, whereas their interaction with a flanking exon causes skipping of the internal alternative exon (22,59). Here, we found that the isolated pseudo-RRM of SRSF1 is sufficient to modulate splicing of nearly half of the tested SRSF1 target genes (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…6D), in line with observed redundancies in RNA binding. Because inclusion of alternative exons is often facilitated by SR protein binding (Han et al 2011;Erkelenz et al 2013), we tested for binding of cognate SR proteins within those exons (Fig. 6E).…”
Section: Sr Proteins Link Alternative Splicing To Mrna Exportmentioning
confidence: 99%
“…The ESEfinder software was programmed to predict exon skipping by scoring the sequences matched with the putative ESEs, as previously reported. 23,24 The ESEs effectively contribute to the exons with the authentic splice sites displaying reduced homology with the consensus sequences. We therefore assessed the homology of all of the splice sites in the SLC12A3 gene to identify the vulnerable exons depending on the ESEs, as described in a previous article, using the Berkeley Drosophila Genome Project splicing predictor program (http://www.fruitfly.org/ seq_tools/splice.html).…”
mentioning
confidence: 99%